The influence of “Choriocene” on leukopoiesis in lactating sows - Шатохін, П. П.; Супруненко, К. В.; Каришева, Л. П. (Scientific Progress & Innovations, 2018)
The paper presents the results of clinical studies on investigating the dose-dependent influence of “Choriocene” on leukopoiesis in lactating sows. It has been established that double administration of the preparation to pregnant sows, 12 days before farrowing and on farrowing day, increases the number of leukocytes in the blood in statistical valid limits relatively to the control group (9.3±1.2 G/l – in the 1st control group, 16.4±1.4 G/l (p ≤ 0.01), and 15.0±1.8 G/l (p ≤ 0.05) in the 2nd and 3rd test groups, correspondingly. Conducting the investigations on the 6th and 16th day after farrowing shows that leukocytosis is observed in the blood of sows of the control and 2nd experimental groups, and in the 3rd group the number of leukocytes is within the physiological norm. The analysis of leukoformula indices shows, that the number of lymphocytes in the sows’s blood of the control group in the first study was higher, and in the experimental ones, within the physiological norm. On the 6th and 16th day of the study, leukocytosis was observed. Raising the number of young neutrophils occurs against the background of decreasing segmented neutrophils in all the examined groups. Determining the neutrophil shift index in the groups where “Choriocene” was used shows that regenerative nucleus shift to the left is observed in the sows’ blood and it is 0.5±0.1 % in the second test group and 0.9±0.1 % in the third one. The intramuscular administration of “Chorio-cene” preparation to pregnant sows in doses of 10 ml twice (14 days before and in the first day after farrowing) shows the stabilizing effect on the leukopoiesis process, creating favorable conditions for the course of regenerative processes in the sows’s genitals during the postpartum period.